PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING ELEMEN KEBHINNEKAAN TUNGGAL IKA DI KELAS V SDN 04 PAUH KOTA PADANG - Putra, Ilham Pratama; Waldi, Atri; Reinita, Reinita; Zuryanty, Zuryanty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe the improvement of Pancasila Education learning outcomes by using the Problem Based Learning (PBL) model in class V SDN 04 Pauh Padang City. This research applies the type of Classroom Action Research (PTK) using qualitative and quantitative approaches. The subjects in this study were teachers (researchers) and students totaling 27 students consisting of 10 men and 17 women. The results of this study showed an increase in: a) teaching module cycle I with an average of 85.41% (Good) and cycle II 95.83% (Very Good b) implementation on the aspect of the teacher cycle I with an average of 82.92% (Good) and cycle II 92.85% (Very Good), while the implementation on the aspect of students cycle I with an average of 82.92% (Good) and cycle II 92.85% (Very Good), c) assessment of students in improving learning outcomes in cycle I obtained 74.82% and cycle II with an average of 87.19%. Based on these results it can be concluded that the Problem Based Learning (PBL) model can improve the learning outcomes of Pancasila Education in class V.